Anticoagulation in patients with impaired renal function and with haemodialysis - Harenberg, J.; Hentschel, V. A.-T.; Du, S.; Zolfaghari, S.; Krämer, R.; Weiss, C.; Krämer, B. K.; Wehling, M. (Hämostaseologie, 2015)
Patients with impaired renal function are exposed to an increased risk for bleeding complications depending on the amount of the anticoagulant eliminated by the kidneys. The elimination of unfractionated heparins, vitamin K antagonists and argatroban is only minimally influenced by a reduced renal function. Low-molecular weight heparins, fondaparinux, danaparoid, hirudins and nonvitamin K antagonist oral anticoagulants (NOAC) cause a variably increased bleeding risk in renal impairment. Dose reductions are recommended for all of these anticoagulants in renal impairment, some are even contraindicated at certain levels of renal impairment. Their benefit over the conventional anticoagulants is preserved if renal dosing is employed. For end-stage renal disease patients specific treatment regimens are required.
Keywords: Heparin; low-molecular weight heparin; direct thrombin inhibitors; oral direct factor Xa inhibitors; vitamin K antagonist; renal impairment